Unraveling bitter peptides in wheat protein hydrolysates - Wenmeng He; Shiqin Wang; Beibei Wang; Mingming Wang; Pan Liao (Food Chemistry: Molecular Sciences)
Wheat protein hydrolysates (WPHs) hold promise for functional food applications, but papain (EC 3.4.22.2)-mediated hydrolysis often results in undesirable bitterness and low yields of small peptides. To address this, we employed in silico strategies to systematically characterize bitter peptides in papain-derived WPHs and elucidate their molecular interactions with the human bitter taste receptor TAS2R14. Enzymatic hydrolysis of wheat proteins was simulated using the BIOPEP-UWM database, identifying 36 potential bitter peptides. Molecular docking studies revealed four critical binding residues (Asn157, Ile262, Trp89, and Phe247) on TAS2R14 that mediate bitterness perception. Notably, peptides rich in proline (Pro), phenylalanine (Phe), and tryptophan (Trp) exhibited heightened bitterness, while glycine (Gly)- and glutamic acid (Glu)-containing peptides were associated with reduced bitterness. These findings provide a mechanistic basis for mitigating bitterness in WPHs through selective enrichment or exclusion of peptides with specific amino acid profiles. By enabling targeted design of hydrolysis processes, this work advances the application of WPHs as palatable, bioactive ingredients in the food industry.